Analysis of Fracture Characteristic of a Gas Main Pipe on the Basis of the Additive Mathematical Model of the Cyclic Random Process and Polynomial Function; IOP Conference Series: Earth and Environmental Science; Vol. 115 : Ecology and safety in the technosphere - Lytvynenko I. V.; Maruschak P. O.; Panin S. V. Sergey Viktorovich; Sorochak A. P. (2018, 2018)
Title screen